Birth-related long bone fractures in otherwise healthy newborns and medical professional liability: literature review and case presentation - M. Trabucco Aurilio; M. Trabucco Aurilio; L. Fava; M. Chisari; M. Bolcato; M. Bolcato (Frontiers in Medicine)
Birth-related long bone fractures are rare but clinically significant events that require careful evaluation to distinguish them from fractures caused by underlying pathological conditions or non-accidental trauma. Their diagnosis and management have important clinical and medico-legal implications. A selective literature review was conducted to identify relevant studies published between 2004 and 2024, regarding incidence, mode of delivery, fracture location, time to diagnosis, treatment, and outcomes. Additionally, an original case report of a female neonate diagnosed with femoral shaft fracture on the third day of life. Neonatal long bone fractures can occur even in the absence of predisposing genetic or metabolic conditions. While they generally heal without for surgical intervention, timely diagnosis through appropriate imaging is crucial to ensure proper management. Failure to do so may expose healthcare professionals and institutions to potential medico-legal liability, both during delivery and in the immediate postnatal period. Preventive strategies should focus on careful prenatal risk assessment, adherence to best practices in delivery maneuvers, and early postnatal monitoring to optimize outcomes and minimize legal risks.